Response of Growth and Yield of Mustard Toward Gibberellin on Peat Soil - ASMADI, ASMADI (Jurnal Sains Pertanian Equator, 2021)
The increase in market demand for mustard needs to be balanced with an increase in production, one of which is by utilizing peat land which is balanced with the provision of gibberellin as a plant growth regulating hormone. This study aims to determine the best concentration of gibberellin (GA3) in increasing the growth and yield of mustard on peat soil. The research was conducted at West Kalimantan Province, Southeast Pontianak Sub-district. The research was conducted from September 12nd "“ October 12nd 2020. The method used was a Completely Randomized Design with 4 levels concentration of gibberellin, namely was p1 (10 ppm); p2 (20 ppm); p3 (30 ppm); p4 (40 ppm). Each treatment was repeated 6 times and consisted of 4 plant samples so the whole plant samples were 96 plants. The variables observed were plant height, number of leaves, leaf area, root volume, plant dry weight and plant fresh weight. The results showed the various concentrations of gibberellin could increase plant height, leaf number, leaf area and fresh weight of caisim mustard plants. The efficient gibberellin concentration was obtained at 30 ppm based on the yield potential of the plant, namely plant fresh weight with an average of 23.72 grams.